Children’s Physical Motoric Development During The Covid-19 Pandemic Through Home Visit - Rebecca Hayyu Rachmaprilia; Bachtiar Syaiful Bachri; Hendratno (IJORER : International Journal of Recent Educational Research, 2022)
Research aims to determine the role of teachers, physical aspects of motor skills, home visit activities for children, and the physical motor development of children aged 4-5 years during the Covid-19 pandemic through home visit activities at Alif Kindergarten Surabaya. This research is a descriptive qualitative research because it describes the phenomenon as it is, namely the description of the physical motor aspects of children aged 4-5 years at Alif Kindergarten Surabaya during the Covid-19 pandemic through home visits. The approach used in this research is a case study because this phenomenon is only centered in TK Alif Surabaya. Case study data can be obtained from all parties concerned, in other words in this study collected from various sources (Nawawi, 2003). The results of this study can be concluded that the teacher's home visit activity is one solution as an online learning support activity for children aged 4-5 years at Alif Kindergarten Surabaya. The development achievements of children aged 4-5 years at Alif Kindergarten Surabaya during teacher home visits during the Covid-19 pandemic are: 1) Children can imitate animal movements; 2) Write numbers, letters, hijaiyah; 3) Jump, 4) Playing with plasticine; 5) Movement and song; 6) Coloring, cutting, and pasting.